Evaluación de impacto de las transferencias monetarias del canon y sobrecanon minero en la pobreza de la región de Piura, 2019 - Valarezo Balcázar, Brayan Fabian (2024)
Peru is a country very diverse and rich in natural resources such as minerals, and their exploitation should benefit the population where these resources are located. The general objective of the research was to analyse the impact of mining transfers in the districts of the Piura region for the period 2019. The specific objectives are: i) To evaluate the impact of mining transfers on monetary and non-monetary poverty for the region of Piura. ii) To evaluate the impact of mining transfers on education for the region of Piura. The database was obtained from the National Population and Housing Census and the Ministry of Economy and Finance, 2019. The methods used for the impact assessment were Generalised Least Squares, Generalised Method of Moments and Propensity Score Matching. The results show that mining transfers generate a positive impact on monetary and non-monetary poverty, i.e. as monetary transfers increase, monetary and non-monetary poverty in the Piura region are reduced, and for the education variable, monetary transfers also have a positive impact on years of education, i.e. as monetary transfers increase, years of education increase in districts that receive higher monetary transfers.